Labour supply and inequality effects of in-work benefits: Evidence from Serbia - Saša Ranelović; Jelena Žarković Rakić; Marko Vladisavljević; Sunčica Vujić (Naše gospodarstvo / Our Economy, 2019)
Low labour market participation, together with the high effective tax wedge at low wage levels, create a fertile ground for the introduction of the in-work benefits (IWB) in Serbia. Our paper provides an ex-ante evaluation of the two IWB schemes, directed at stimulating the labour supply and more equal income distribution. The methodological approach combines the tax-and-benefit microsimulation model with the discrete labour supply model. Our results show that both individual and family-based IWB schemes would considerably boost labour market participation, although family-based benefits would have disincentivizing effects for the secondary earners in couples. Most of the behavioural changes take place among the poorest individuals, with significant redistributive effects.
Keywords: J22; H24; D31; I32; 330; in-work benefits; labour supply; inequality; discrete choice model; microsimulation